Relieving Sore Throat Formula Exerts a Therapeutic Effect on Pharyngitis through Immunoregulation and NF-κB Pathway - Yushi Ding; Suyun Yu; Zhonghong Wei; Rui Deng; Peng Chen; Yifan Sun; Qi Jia; Xiaoman Li; Yuanyuan Wu; Wenxing Chen; Kurt S. Zanker; Aiyun Wang; et al. (Hindawi Limited, 2020)
Relieving Sore Throat Formula (RSTF) is a formula approved by the China Food and Drug Administration and has been used for the treatment of pharyngitis in clinic for many years. However, the potential pharmacological mechanism still remains unknown. We combined multiple methods including bioinformatics data digging, network pharmacology analysis, and pathway analysis to predict the potential target of RSTF. We verified our in silico prediction results with an in vivo/vitro antibacterial effect test, mouse phagocytic index test, proliferation, transformation, and migration of mouse spleen lymphocytes. Alteration of NF-κB pathway was determined by Western blotting, immunofluorescence, and PCR. The in vivo experiments demonstrated that the RSTF could significantly relieve the symptoms of pharyngitis. A rat saliva secretion test showed that RSTF can effectively relieve the xerostomia symptom. A phenol red excretion test showed that RSTF has an eliminating phlegm effect. A hot plate method and granuloma experiment proved that RSTF also have analgesic and anti-inflammatory effects. In silico prediction demonstrates that 70 active compounds of RSTF were filtered out through ADME screening and 84 putative targets correlated with different diseases. Pathway enrichment analysis showed that the candidate targets were mostly related to the response to bacteria and immunity signalling pathways, which are known contributors to pharyngitis. Experimental results confirmed that RSTF exerted therapeutic effects on pharyngitis mainly by antibacterial effect and downregulation of NF-κB activities. It is demonstrated both in silico and in vivo/vitro that RSTF exerted therapeutic effects on pharyngitis mainly through an antibiotic effect and downregulation of NF-κB signalling pathway.